Development of Islamic-Based Vitruvius Design Learning Media to Improve Early Childhood Development in Kindergarten - Sitepu, Juli Maini; Masitah, Widya; Ginting, Nurman (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to improve all aspects of early childhood development. The study employs a modified Research and Development (R&D) model based on Borg and Gall’s framework, comprising six stages: identifying potential and problems, collecting initial data, designing media, validating media, revising the design, and conducting product trials. Media developed using Adobe Illustrator software that can create custom letters, gradient effects, and textures. Was tested on 56 children at TK ABA Medan Helvetia District. Data collection involved two types of questionnaires: media validation and children's comprehension assessment. Validators and teachers evaluated each questionnaire using a checklist scale. Data analysis employed qualitative and quantitative methods to assess the effectiveness of educational media. Data analysis employed qualitative and quantitative methods to assess the effectiveness of educational media. Results demonstrated a significant improvement in children’s development with pre-test scores averaging 25,6 and post-test scores at 33,6. This shows that the Islamic-based Vitruvius design learning media can improve child development. This research can also be a reference for early childhood education teachers to use interesting learning media according to the child's developmental stage.